Strengthening vaccines and medicines manufacturing capabilities in Africa: challenges and perspectives - AbdulRahman A Saied; Asmaa A Metwally; Manish Dhawan; Om Prakash Choudhary; Hani Aiash (EMBO Molecular Medicine)
Abstract Africa carries a high burden of infectious diseases. Every year, millions of Africans contract tuberculosis, malaria, and many other diseases. Malaria kills hundreds of thousands of children under the age of five years annually. More than 11,000 people died during the 2014–2016 Ebola outbreak in West Africa; still, occasional cases of Ebola, as well as monkeypox, periodically appear in the Democratic Republic of Congo. Since most of the African countries gained their independence during the 1960s, the continent has relied heavily on the outside world for diagnostics, medicines, vaccines, personal protective equipment, and other medical supplies. Africa consumes nearly 25% of the globally produced vaccines but imports 99% and 95% of its vaccines and medicines, respectively. The 55 African countries were not able to ensure the health of 1.3 billion Africans during the COVID‐19 pandemic but had to rely on other global initiatives and other countries for help and support. However, the pandemic and the shortage of vaccines may have been the much‐needed trigger for this situation to change. “When misfortunes increase, they erase each other.” Naguib Mahfouz (1911–2006).